2021
DOI: 10.1021/jacs.0c12478
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2 Electrochemical Reduction Enabled by a Tricomponent Copolymer Modifier on a Copper Surface

Abstract: Electrochemical CO2 reduction over Cu could provide value-added multicarbon hydrocarbons and alcohols. Despite recent breakthroughs, it remains a significant challenge to design a catalytic system with high product selectivity. Here we demonstrate that a high selectivity of ethylene (55%) and C2+ products (77%) could be achieved by a highly modular tricomponent copolymer modified Cu electrode, rivaling the best performance using other modified polycrystalline Cu foil catalysts. Such a copolymer can be convenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 66 publications
5
113
0
1
Order By: Relevance
“…phenylpyridinium in porous random copolymers can increase polymer film robustness. 223 Xie et al screened six amino acids as additives to copper nanowire catalysts. 224 Glycine led to the greatest improvement, increasing the FE of ethylene production from 9.5% to 24.0%.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…phenylpyridinium in porous random copolymers can increase polymer film robustness. 223 Xie et al screened six amino acids as additives to copper nanowire catalysts. 224 Glycine led to the greatest improvement, increasing the FE of ethylene production from 9.5% to 24.0%.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“… 7 , 12 15 Promising strategies for improving CO 2 R selectivity for C 2+ products include changing catalyst morphology 16 19 and electrolyte composition, 14 , 20 employing bimetallic systems and alloys, 21 23 and adding organic modifiers. 24 29 While these techniques may facilitate altered product distributions, they are not amenable to identifying empirical scaling relationships due to substantial variation in catalyst preparation and electrochemical testing conditions across independent studies. It is consequently pertinent to conduct studies that systematically and broadly vary select parameters.…”
Section: Introductionmentioning
confidence: 99%
“…38 Also, the alloying elements substantially alter other aspects of the product distribution, making this collection of catalyst electrodes particularly well-suited for inferring intrinsic reactivity trends; the catalyst morphology is kept relatively constant with respect to the compendium of results in the literature. 9,12,14,15,[18][19][20][22][23][24]30,39 For example, through study of well-defined Cu surfaces, Hori and others identified that the relative production of CH4 and C2H4 is highly facet-dependent. 13 The distribution of exposed facets of a polycrystalline fcc-phase metal electrode could be altered via alloying due to changes in growth kinetics and/or relative surface energies upon addition of the alloying element, which would in principle provide a method to break the CH4-C2+ scaling relationship by tuning catalyst composition.…”
Section: Figurementioning
confidence: 99%
“…[10][11][12][13] Promising strategies for improving CO2R selectivity for C2+ products include changing catalyst morphology [14][15][16][17] and electrolyte composition, 12,18 employing bimetallic systems and alloys, [19][20][21] and adding organic modifiers. [22][23][24][25][26][27] However, identifying empirical scaling relationships from the published data is challenging due to substantial variation in catalyst preparation and electrochemical testing conditions across independent studies, highlighting the need for studies that systematically and broadly vary select parameters.…”
Section: Introductionmentioning
confidence: 99%